Evaluating the services of Malaysian hotels from the leisure traveler's perspectives - Mhd Suhaimi Ahmad; Ahmad Azmi M.Ariffin; Azhar Ahmad (Penerbit Universiti Kebangsaan Malaysia, 2008)
This study evaluated the expectation, perception and satisfaction level of leisure travelers towards hotel attributes and services quality in Malaysia. It specifically tried to delineate basic dimensions of local leisure travelers towards hotel attributes and subsequently evaluate their satisfaction level towards hotel attributes. This study involved a questionnaire-survey of 180 respondents and employed Factor Analysis with VARIMAX rotation as the main analysis. Eight underlying factors representing 58.6 per cent of the explained variance were extracted. The most important factor in explaining the variance was "staff service quality", followed by "value" and "core products' quality." The result of reliability analysis showed that the alpha coefficients for the eight factors ranged from 0.62 to 0.84 and eigenvalues from 1.00 to 7. 76. Finally, Regression Analysis was employed to examine the eight underlying factors relative importance in contributing to the overall level of satisfaction towards the hotel attributes and services. The findings of the regression analysis suggested that local travelers' overall satisfaction was primarily derived from the factor of "value" followed by "core products' quality" and "staff service quality." Factor of ''facility of mini bar" was the only negative factor derived from the analysis. The findings of this study and its marketing implication could assist hoteliers to design their hotel services in order to target the segment of leisure travelers in the most efficient way.